A Case-Study of Implementation of Improved Strategies for Prevention of Laboratory-acquired Brucellosis - Louisa J. Castrodale; Gregory A. Raczniak; Karen M. Rudolph; Lori Chikoyak; Russell S. Cox; Tricia L. Franklin; Rita M. Traxler; Marta Guerra (Elsevier, 2015)
Background: In 2012, the Alaska Section of Epidemiology investigated personnel potentially exposed to a Brucella suis isolate as it transited through three laboratories. Methods: We summarize the first implementation of the United States Centers for Disease Control and Prevention 2013 revised recommendations for monitoring such exposures: (1) risk classification; (2) antimicrobial postexposure prophylaxis; (3) serologic monitoring; and (4) symptom surveillance. Results: Over 30 people were assessed for exposure and subsequently monitored for development of illness. No cases of laboratory-associated brucellosis occurred. Changes were made to gaps in laboratory biosafety practices that had been identified in the investigation. Conclusion: Achieving full compliance for the precise schedule of serologic monitoring was challenging and resource intensive for the laboratory performing testing. More refined exposure assessments could inform decision making for follow-up to maximize likelihood of detecting persons at risk while not overtaxing resources.